The Arab awakening : America and the transformation of the Middle East - Pollack, Kenneth M. (Kenneth Michael), 1966- (Washington, DC : Brookings Institution, 2011)
'Analyzes key aspects of the 2011 Mideast turmoil, such as Arab public opinion; socioeconomic and demographic conditions; the role of social media; influence of Islamists; the impact of political changes on the Arab-Israeli peace process; and ramifications for the United States and the rest of the world. Also provides country-by-country analysis of Middle East political evolution'--Provided by publisher.
Preface: Why should you read this book? -- 1. Introduction : understanding the Arab Awakening / Kenneth M. Pollack -- PART I. THE DYNAMICS OF THE ARAB SPRING -- 2. Arab public opinion : what do they want? / Shibley Telhami -- 3. Democratization 101 : historical lessons for the Arab Spring / Stephen R. Grand -- 4. Islamists and the Brotherhood : political Islam and the Arab Spring / Shadi Hamid -- 5. The impact of new media : the revolution will be tweeted / Michael S. Doran -- 6. The impact on the peace process : peacemaker or peacebreaker? / Khaled Elgindy and Salman Shaikh -- 7. The Arab militaries : the double-edged swords / Kenneth M. Pollack -- 8. The economic dimension : the price of freedom / Suzanne Maloney -- 9. Terrorism : Al-Qaeda and the Arab Spring / Daniel L. Byman -- PART II. COUNTRIES IN TRANSITION -- 10. Democratizers? The pursuit of pluralism / Kenneth M. Pollack -- 11. Iraq : the roller coaster of democracy / Kenneth M. Pollack -- 12. Egypt : the prize / Shadi Hamid -- 13. Tunisia : birthplace of the revolution / Shadi Hamid -- 14. Libya : from revolt to state-building / Akram Al-Turk -- 15. The Palestinians : between national liberation and political legitimacy / Khaled Elgindy -- PART III. THE IMPERATIVE OF REFORM -- 16. Reform : convincing reluctant regimes to change / Kenneth M. Pollack -- 17. Making reform credible : the critical piece of the puzzle / Stephen R. Grand, Shadi Hamid, Kenneth M. Pollack, and Sarah E. Yerkes -- 18. Saudi Arabia : the elephant in the living room / Bruce O. Riedel -- 19. Jordan : an imperfect state / Salman Shaikh -- 20. Kuwait, Qatar, Oman, and the UAE : the nervous bystanders / Suzanne Maloney -- 21. Bahrain : island of troubles / Michael S. Doran and Salman Shaikh -- 22. Morocco : the model for reform? / Sarah E. Yerkes -- 23. Algeria : whistling past the graveyard / Bruce O. Riedel -- PART IV. STATES IN CRISIS -- 24. States in civil war : challenges for the United States / Daniel L. Byman -- 25. Yemen : the search for stability and development / Ibrahim Sharqieh -- 26. Syria : the ghosts of Hama / Michael S. Doran and Salman Shaikh -- PART V. OTHER REGIONAL ACTORS -- 27. Regional actors : the changing balance of power in the Middle East / Daniel L. Byman and Kenneth M. Pollack -- 28. Israel : a frosty response to the Arab Spring / Daniel L. Byman -- 29. Iran : the bogeyman / Suzanne Maloney -- 30. Turkey : an interested party / Omer Taspinar -- PART VI. THE EXTERNAL POWERS -- 31. External powers : riding the tsunami / Kenneth M. Pollack -- 32. Europe : muddling through / Ruth Hanau Santini -- 33. Russia : Moscow does not believe in change / Pavel K. Baev -- 34. China : unease from afar / Jonathan D. Pollack -- 35. The international order and the emerging powers : implications of the Arab Awakening / Bruce Jones -- 36. The United States : a new American grand strategy for the Middle East / Kenneth M. Pollack -- Appendix: Political, social, and economic indicators of the Middle East.
Includes bibliographical references and index.
Keywords: Arab Spring, 2010-; Democratization -- Arab countries -- History -- 21st century; Protest movements -- Arab countries -- History -- 21st century; Arab countries -- Politics and government -- 21st century; United States -- Foreign relations -- Arab countries; Arab countries -- Foreign relations -- United States; Arab countries -- Foreign relations -- 21st century